Shock Advertising of Online Insurance Services: Features and Analysis - Viktoriia SHUMKOVA; Olena SHUMKOVA (Communications of International Proceedings, 2021)
Online marketing plays an important role in service of insurance. It is a fact. But nowadays, due the pandemic of COVID-19, online advertising is very important for insurance, because they have a very specific product for sale. It is well known that advertising is a process of communication with customers so that relying on the advantages and positive features of a product to influence in thoughts and mental potential or probable customers. The goal of this article is to study the features of the shock advertising campaign and to determine the level of its impact on the provision of online and offline insurance services. When conducting this research, authors used the statistical information of Ukraine for the last 3 years (2018-2020), the statistical information of European Union for the last year and the statistical information AXA Insurance 2021 and Insurance Outlook 2021. In the course of the study, general scientific methods, methods of comparisons, surveys, complex assessments were used. The authors analyzed the nature, types and content of shock advertising messages of different types of insurance products (life and non-life). At the arcicle authors analyzed the attitude of consumers of insurance services to shock advertising, its elements and main attractive features of it and investigated the effectiveness of such advertising messages on consumer appeals to insurance companies. According to the results of the research, it can be concluded that the shock advertising of insurance services will be quite effective, since on the basis of the formed negative or positive attitude to it, the consumer is aware of the need to implement insurance for safety.
Keywords: Insurance Services; Online Advertising; Shock Advertising; Online Marketing.